Dc Voltage Insulating Properties of Various Inorganic Materials in Hydrogen Atmosphere at High Temperatures. Issue 4 (December 2015) - Takahashi, Koichi; Hanada, Nobuko; Ishida, Masayoshi
SUMMARY In this study, the dc voltage insulating properties in a hydrogen atmosphere at high temperatures (600 <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fh8xh9s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />∘C</alternatives> to 850 <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fh8xhbb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />∘C</alternatives>) were evaluated for alumina (Al<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fh8xhvm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives>O<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fh8xht2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3</alternatives>), magnesia (MgO), silicon nitride (Si<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fh8xhxq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3</alternatives>N<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fh8xhw5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />4</alternatives>), and mica (KMg<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fh8xhrz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3</alternatives>(Si<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fh8xhqd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3</alternatives>Al)O<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fh8xhsh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />10</alternatives>(OH)<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fh8xd2c" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives>) to comprehend the difference in the insulating properties of oxide, nitride, and minerals. The activation energies of the electrical conductivity of alumina and magnesia in hydrogen were larger than those in air. On the other hand, the electrical conduction values for silicon nitride and mica in hydrogen were the same as those in air. Therefore a low oxygen partial pressure would have some influence on the electrical conduction of oxides. Increasing the temperature did not result in a large change in the electrical conduction mechanism in any of the materials in either atmosphere. The maximum partial discharge (PD) in hydrogen tended to increase compared to that in air at high voltage. The applied voltage at which the maximum amount of PD started to increase rapidly became lower with increasing temperature in all materials and in both atmospheres. The total amount of PD tended to decrease with increasing temperature in all materials and in both atmospheres. However, above a certain temperature, the total amount of PD either increased or showed a slight decrease.